The Effects of Physical Exercise on Stereotypic Behaviors in Autism: Small-n Meta-Analyses. (March 2020) - Tarr, Christopher W.; Rineer-Hershey, Ashlea; Larwin, Karen
Physical exercise has shown the potential to reduce stereotypic behaviors. The current investigation conducted three meta-analyses on the effects of physical exercise on stereotypic behaviors in individuals with autism. Study 1 produced four aggregate score studies ( n = 54) that included nine effect sizes ranging from d = –.85 to .31. Study 1 yielded an overall effect size of d = –.463. Study 2 produced six single subject design studies ( n = 13) that included 48 effect sizes ranging from d = −1 to .5156. Study 2 yielded an overall effect size of d = –.456. Study 3 combined all 10 studies ( n = 67) that included effect sizes ranging from d = −1 to .5156. The n = 10 articles combined produced an overall effect size of d = –.456. The effect sizes demonstrate that physical exercise does have the potential to decrease stereotypic behaviors in individuals with autism.